A Meta-Analysis of Hypnotic Interventions for Depression Symptoms: High Hopes for Hypnosis?. Issue 3 (1st January 2019) - Milling, Leonard S.; Valentine, Keara E.; McCarley, Hannah S.; LoStimolo, Lindsey M.
Abstract : This meta-analysis quantifies the effectiveness of hypnosis for treating the symptoms of depression. To be included in the meta-analysis, studies were required to use a between-subjects or mixed-model design in which a hypnotic intervention for depression was compared with a control condition in reducing depression symptoms. Of 197 records screened, 10 studies incorporating 13 trials of hypnosis met the inclusion criteria. The mean weighted effect size for 13 trials of hypnosis at the end of active treatment was 0.71 ( p  ≤ .001), indicating the average participant receiving hypnosis showed more improvement than about 76% of control participants. The mean weighted effect size for four trials of hypnosis at the longest follow-up was 0.52 ( p  ≤ .01), indicating the average participant treated with hypnosis showed more improvement than about 51% of control participants. These effect sizes are comparable to those associated with well-known psychological interventions for depression (e.g., Beck's cognitive therapy, interpersonal therapy) and suggest hypnosis is a very effective way of alleviating the symptoms of depression. Clinicians may wish to give serious consideration to hypnosis as a treatment option when working with clients and patients who are depressed.